Mobility and Distribution of a- and b-Isomers of Endosulfan in Soils of Uttarakhand - P. Raha and H. Banerjee, Sanjay Kumar Singh (Journal of the Indian Society of Soil Science, 2016)
The present study aimed at delineating the effect of soil properties on adsorption, movement and distribution of endosulfan in the soil samples drawn from districts of Uttarakhand, India. The results indicated that the soils with different physicochemical properties have influenced adsorption isotherms, movement and distribution pattern of endosulfan insecticides, especially at higher concentration levels. The adsorption of endosulfan to soils was best found to fit a Freundlich equation and Freundlich’s adsorption constant ‘K’ and ‘1/n’, and the correlation coefficient values were in the range of 0.92 and 0.99, respectively. The highest distribution coefficient (Kd) value of 54.32 (b-endosulfan) was received to the Almora soil followed by Udham Singh Nagar soil, 44.08 (b-endosulfan) with a high clay content and organic matter content exhibited the high adsorption capacity. In the present study, endosulfan downward movement was performed in the packed soil column; the distribution of endosulfan was obtained throughout the column and even showed presence in the lower most soil core. The maximum distribution per cent of a- and b-isomers of endosulfan was recorded in soils of Almora (92.61 and 94.07%) followed by Udham Singh Nagar soil (94.36 and 95.16%) with minimum in leachates (5.64 and 4.84%) and (7.39 and 5.93%), respectively was obtained. This study proved the highly persistent nature of chemical with relatively high organic matter and clay content of soil that restricted the downward leaching.